Skrining Fitokimia, Total Fenol, dan Aktivitas Antioksidan Ekstrak Metanol Tangkai Sisir Buah Pisang Agung - Ade Wahyu Pratama; Sri Rahayu Lestari; Abdul Gofur; Yunita Rakhmawati (Universitas Muhammadiyah Semarang, 2022)
Free radicals have an unpaired electron in the outermost orbital causing degenerative diseases such as cancer. However, it can be inhibited by antioxidants. Natural antioxidants are considered safer than synthetic antioxidants, which have harmful side effects if consumed by the body in the long term. Natural antioxidants are obtained from natural ingredients such as plants. Agung banana is one of the plants that have the potential to produce antioxidants. The community widely consumes these bananas, increasing the waste of banana bunches stem. Banana bunch stem is one of the wastes that has not been widely used. This study aims to determine secondary metabolites' content through phytochemical screening, total phenol, and antioxidant activity.Phytochemical screening is a qualitative descriptive test with indicators of color change and the presence of precipitate. The screening results showed that the agung banana bunch stem extract was positive for flavonoids, triterpene terpenoids, polyphenols, tannins, and alkaloids. The total phenol test showed a result of 40,00 mg/g. The antioxidant activity test showed an IC50 value of 190,55 µg/ml, which was classified as weak. Research shows that the relatively small relationship between total phenol causes low/weak antioxidant activity.